2003
DOI: 10.1080/0036554021000028082
|View full text |Cite
|
Sign up to set email alerts
|

Defibrinogenation Therapy for Idiopathic Sudden Sensorineural Hearing Loss in Comparison with High-dose Steroid Therapy

Abstract: These results indicate that high-dose steroid therapy should be employed in preference to defibrinogenation therapy for patients with moderate hearing loss, whereas defibrinogenation therapy has an advantage for those with severe hearing loss, in view of its lower frequency of side-effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 13 publications
1
42
1
Order By: Relevance
“…Multiple poorly controlled studies have failed to show clinical improvement of this form of therapy. 190 Finally, diatrizoate meglumine (Hypaque) is an intravenous contrast agent that has been postulated to improve hearing in patients with SSHNL. An analysis of Hypaque vs steroids vs vasodilator showed no better results with any of those treatments than the published spontaneous recovery rate of 65%.…”
Section: Supporting Textmentioning
confidence: 99%
“…Multiple poorly controlled studies have failed to show clinical improvement of this form of therapy. 190 Finally, diatrizoate meglumine (Hypaque) is an intravenous contrast agent that has been postulated to improve hearing in patients with SSHNL. An analysis of Hypaque vs steroids vs vasodilator showed no better results with any of those treatments than the published spontaneous recovery rate of 65%.…”
Section: Supporting Textmentioning
confidence: 99%
“…Wilson et al 4 reported a recovery rate of 61% in patients taking steroids, while in our sample significant recovery was found in only 34.6% of these patients. Suzuki et al 8 reported a significant recovery average of 52.2% including patients on steroids or batroxobin, while our significant recovery rate remained at 38.6%. One of the possible reasons that may have contributed to this discrepancy is the fact that our study used pure--tone averages covering all affected frequencies and all higher frequencies, while the original studies used only the 0.5, 1 and 2 kHz bands and the 0.25, 0.5, 1, 2, and 4 kHz bands respectively.…”
Section: Discussionmentioning
confidence: 84%
“…Criterion B used by Suzuki et al 8 , when assessing absolute hearing recovery in decibels, fails to consider the initial degree of established hearing loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations